Sports in the construction of the imaginary of the modern woman in Panama - Samudio A. , Edda O. (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article deals with the tough and prolonged struggle of women to overcome the obstacles imposed on their participation in sports in a society conceived and ruled under masculineprecepts, which we identify as female androcentric imaginary. In this context, the main objective of this study is to analyze the incorporation process of the female physical culture in the educational environment of Panama during an important period and its role in the changes of the androcentric female social imaginary. This article is supported by the study and analysis of significant bibliographic and newspaper data collected.